PENERAPAN TERAPI MASSAGE EFFLEURAGE TERHADAP PENURUNAN INTENSITAS DISMENORE PADA MAHASISWI ASRAMA UNIVERSITAS MUHAMMADIYAH AHMAD DAHLAN PALEMBANG - Ulaa, Maratun; Siti Meilia Maharani (Jurnal Kesehatan Madani Medika, 2025)
Background: Dysmenorrhea is pain during menstruation, characterized by cramps in the lower abdomen that radiate to the waist, legs, and groin. One non-pharmacological approach to reducing primary dysmenorrhea is effleurage massage. This technique, performed with gentle, light massage, creates a relaxing effect, reducing pain, improving blood circulation, and relaxing abdominal muscles. It has no side effects and can be performed independently. Objective: To determine the reduction of primary dysmenorrhea in adolescent girls. Method: Case study with two respondents. The inclusion criteria for this case study were adolescent girls aged 16-19 years who experienced primary dysmenorrhea. The exclusion criteria were patients taking painkillers. Effleurage massage was performed for 15 minutes over three days. Data collection used assessment sheets, observations, and effleurage massage standard operating procedures (SOPs). Results: After effleurage massage, the pain scale of dysmenorrhea in both respondents decreased, in the first respondent the initial pain scale of 6 became 1 and in the second respondent the initial pain scale of 5 became 1. Conclusion: Effleurage massage management can reduce pain in adolescents experiencing primary dysmenorrhea. Suggestion: It is hoped that it can increase adolescents' knowledge about how to overcome dysmenorrhea by doing effleurage massage when dysmenorrhea occurs independently.